VIRTUAL REALITY ENHANCES STUDENT’S ACHIEVEMENT IN BIOLOGY: A COMPARATIVE STUDY WITH INTERACTIVE WHITEBOARDS AND TRADITIONAL METHODS - Neiroukh, Nader; Hamad, Nardin; Ayyoub, Abdalkarim (LPPM Universitas Jambi, 2025)
Studies of immersive technologies as transformative tools for the teaching of science are on the rise but very few empirical studies have been done to compare immersive to semi-immersive and traditional methods. The purpose of the current study was to analyse the effects of three different levels of immersion-virtual reality (VR), interactive whiteboards (IWB) and traditional teaching-on tenth-grade students’ biology achievement in the topic of cell division. A quasi-experimental design of teaching that had three groups (VR group, n = 72; IWB group, n = 58; control group, n = 64) was used. The same qualified biology teacher taught all three groups, using semi-immersive, fully immersive, and traditional teaching through nine teaching sessions. An achievement test (validated for content reliability) was given as a pretest and a post-test. The pretest established the groups equivalently; and the post-test measured student learning gains since the three teaching methods could count for their test scores. ANCOVA results revealed that there were statistically significant differences in the groups’ achievements. The VR group scores were the highest and the IWB group, the second highest-while the control group received the lowest post-test scores. The results suggest that more immersive teaching effects positively aided learning comprehension of abstract biological processes like cell division. The significance of the study was its direct comparison of fully immersive, semi-immersive and traditional teaching of the topic, providing practical implications for integrating VR into science classrooms to enhance students’ comprehension of abstract biological processes.